Assessment of Sustainable Development Levels in Russian Organizations Using Fuzzy Sets Theory - Nesvetailov, Vasili; Hdeib, Tareq; Bukhorev, Sulaimon (Jordan Journal of Business Administration, 2020)
In practice, the analysis of the sustainable development level of organizations can be carried out using different approaches. At the moment, there are more than twenty methods of numerical integrated assessment of the financial conditions of organizations that can indicate the level of sustainable development. At the same time, such models are developed for economic conditions that are significantly different from those prevailing in Russia. Therefore, Russian organizations are faced with the task of choosing the optimal approach for evaluating sustainable development levels that are suitable to their economic conditions. One of these approaches is the assessment of the level of sustainable development of organizations using the fuzzy sets theory, developed by L. Zadeh, which allows adequately and quickly to analyze complex indicators that can lead to sustainable development of the organization. Therefore, the problem of using the fuzzy sets theory to assess sustainable development of Russian organizations is the basis of this article. The authors note that using the fuzzy sets theory in relation with 11 financial indicators that are related to sustainable development will give objective results about the current condition of the organizations and their potential to achieve sustainable development in the future.